Learning English as a Second Language Among Secondary Students With Dyslexia: A Comprehensive Study on Reading Difficulties, Effects and Strategies - Davina Ivy Lyn, David (Universiti Malaysia Sarawak (UNIMAS), 2022)
Reading is extremely important in our educational, economic, and social lives. Reading ability is highly valued and essential for socioeconomic development. It is the most important classroom skill since it can help students enhance their overall language ability. However, this situation resulted in reading difficulties among adolescents with dyslexia, especially those in secondary school.